Google Web Toolkit : GWT Java AJAX programming : a practical guide to Google Web Toolkit for creating AJAX applications with Java - Chaganti, Prabhakar (From technologies to solutions., 2007)
"This book is for Java developers who want to create Ajax interfaces using the Google Web Toolkit (GWT). It focuses on useful, practical tasks from the first chapter. The book is aimed at programmers who want to use GWT to create interfaces for their professional web applications. It concentrates on the serious side of Ajax: creating powerful, productive applications for browser platforms"--Resource description page